Magnetic properties of layered rare-earth oxy-carbonates Ln2O2CO3 (Ln=Nd, Sm, and Dy). (August 2016) - Arjun, U.; Brinda, K.; Padmanabhan, M.; Nath, R.
Abstract: Polycrystalline samples of rare-earth oxy-carbonates Ln 2 O2 CO3 ( Ln =Nd, Sm, and Dy) are synthesized and their structural and magnetic properties are investigated. All of them crystallize in a hexagonal structure with space group P 6 3 / mmc . They form a double layered structure with frustrated triangular arrangement of rare-earth magnetic ions. An antiferromagnetic transition is observed at T N 1.25 K, 0.61 K, and 1.21 K for Nd2 O2 CO3, Sm2 O2 CO3, and Dy2 O2 CO3, respectively. From the analysis of magnetic susceptibility, the value of the Curie–Weiss temperature θ CW is obtained to be 21.7 K, 18 K, and 10.6 K for Nd2 O2 CO3, Sm2 O2 CO3, and Dy2 O2 CO3, respectively. The magnetic frustration parameter f ( = | θ CW | / T N ) is calculated to be 17.4, 31, and 8.8 for Nd2 O2 CO3, Sm2 O2 CO3, and Dy2 O2 CO3, respectively, which indicates that Sm2 O2 CO3 is strongly frustrated compared to its Nd and Dy analogues. Abstract : Highlights: Layered rare-earth oxy-carbonates Ln 2 O2 CO3 ( Ln =Nd, Sm, and Dy) are synthesized. Structural and magnetic properties are investigated. All the compounds are strongly frustrated and undergo antiferromagnetic long-range-ordering at low temperatures. Sm compound is having the highest frustration parameter of f 31 which proves that Sm2 O2 CO3 is the strongly frustrated one compared to the other two.